Al-Qabisi’s Theory on Physical Punishment Method for Students - Syahrizal, Syahrizal (Jurnal Ilmiah Peuradeun, 2021)
The ideas of al-Qabisi on the physical punishment method for the students now tend to be poorly comprehended, acknowledged, and implemented by educators in the educational institution system. It is almost certain that the study of the physical punishment method is still limited to theory and knowledge without giving application in the reality of life. This research aimed to analyze the principle of physical punishment for the students, illustrate the terms, as well as the objectives of the punishment, and the impact on the psychological and physical of students. Based on library research and descriptive, deductive, and content analysis of primary and secondary data sources, the result of the research showed that according to al-Qabisi, there are six principles of physical punishment, four conditions that must be considered in the provision of physical punishment, five purposes of giving physical punishment for them, and imposition of physical punishment for them according to al-Qabisi harms the physical and psychological of students.